Characterisation of vascular changes in different stages of Stargardt disease using double swept-source optical coherence tomography angiography. Issue 1 (2nd November 2019) - Reich, Michael; Glatz, Andreas; Cakir, Bertan; Böhringer, Daniel; Lang, Stefan; Küchlin, Sebastian; Joachimsen, Lutz; Lagreze, Wolf; Agostini, Hansjuergen T; Lange, Clemens
Abstract : Objective: To describe vascular changes in different stages of Stargardt disease (STGD) via double swept-source optical coherence tomography angiography. Methods and analysis: Prospective, cross-sectional case–control study. Twenty-three patients (45 eyes) with ABCA4 mutations graded according to the Fishman STGD classification and 23 controls (23 eyes) were included. Two independent investigators quantified the foveal avascular zone (FAZ) in the superficial and deep capillary plexus (SCP/DCP) and the areas presenting rarefied flow and complete vascular atrophy in the outer retina to choriocapillaris (ORCC) and choriocapillaris (CC) slab. Results: The mean age at first diagnosis of STGD was 24.0 years (range 9–50) and 37.9 years (range 18–74) at the time of examination. Eleven patients were assigned to the Fishman STGD classification stage (S) 1, three to S2, eight to S3 and one to S4. The FAZ in SCP and DCP was increased in all stages compared with controls (p<0.01). Areas with rarefied flow signal and vascular atrophy were detected in the ORCC and the CC layer and grew with increasing stage of disease (p<0.01). The duration of disease correlated with the extent of the enlarged FAZ in the SCP/DCP and with the area of reduced flow in the ORCC and CC layer (p<0.01). Best corrected visual acuity correlated negatively with the extent of the enlarged FAZ in the SCP/DCP (p<0.0001), as well as with enlarged atrophic area in the ORCC and CC layer (p=0.026 and p=0.074). Conclusions: Patients with STGD reveal vascular changes in the retina and CC in all disease stages. The avascular zone in the SCP/DCP and areas with rarefied flow signal in the ORCC/CC increase with the duration and stage of disease, indicating progressive vascular decay most likely secondary to retinal pigment epithelium and neuronal loss. Furthermore, increased vascular damage is associated with decreased vision.